Worst Prognosis in the "Complex" Jejunoileal Atresia: Is It Real? - Silvana Federici; Maria Domenica Sabatino; Vincenzo Domenichelli; Simona Straziuso (Georg Thieme Verlag KG, 2015)
Abstract Objective This report documents the authors' experiences in the management of "complex" jejunoileal atresia (JIA) and provides a review of the recent literature on "simple" and "complex" JIA. Materials and Methods This is a retrospective study of eight cases of "complex" JIA managed at the Pediatric Surgical Unit of Infermi Hospital in Rimini from 2002 to 2012. The inclusion criteria are all cases of JIA associated with distal bowel deformities and Types IIIb or IV. One patient had gastroschisis. Results The authors of this study performed primary anastomosis on three patients and enterostomies on five patients. In one case in which a patient presented with gastroschisis, the V.A.C. Therapy System (KCI Medical Ltd., Langford Locks, Kidlington, UK) was used to close the abdominal defect. All patients needed central venous catheter (CVC). Total parenteral nutrition (TPN) was administered for a mean of 12 days. Oral feeding was introduced on mean day 7 (7.71 ± 3.40 standard deviation). Patients with enterostomy began extracorporeal stool transport on mean day 14. No outcomes resulted in short bowel syndrome (SBS). The mortality rate was zero. The authors of this study performed more enterostomies and CVC insertion than other authors in "complex" JIA and reported a percentage of SBS, complications of TPN, and start of oral feeding comparable to "simple" case reported by other authors. Conclusions The results demonstrate that the complexity of JIA alone is not associated to a worsening prognosis than simple atresia if the surgical and clinical approach is as conservative as possible.